Gene mapping and candidate gene analysis of multi-floret spikelet 3 (mfs3) in rice (Oryza sativa L.) - Hao ZHENG; Jun ZHANG; Hui ZHUANG; Xiao-qin ZENG; Jun TANG; Hong-lei WANG; Huan CHEN; Yan LI; Ying-hua LING; Guang-hua HE; Yun-feng LI (Journal of Integrative Agriculture, 2019)
Rice (Oryza sativa L.) is one of the most important food crops worldwide and a model monocot plant for gene function analysis, so it is an ideal system for studying flower development. This study reports a mutant, named multi-floret spikelet 3 (mfs3), which is related to the spikelet development in rice and derived from the ethylmethane sulfonate (EMS)-treated rice cultivar XIDA 1B. In mfs3, the main body of palea (bop) was degenerated severely and only glume-like marginal regions of palea (mrp) remained, while other floral organs developed normally, indicating that the palea identity was seriously influenced by the mutation. It was also observed that the number of floral organs was increased in some spikelets, including 2 lemmas, 4 mrp, 4 lodicules, 8–10 stamens, and 2 pistils, which meant that the spikelet determinacy was lost to some degree in mfs3. Furthermore, genetic analysis demonstrated that the mfs3 trait was controlled by a single recessive gene. Using 426 F2 mutants derived from the cross between sterile line 56S and mfs3, the MULTI-FLORET SPIKELET 3 (MFS3) gene was mapped between the molecular markers RM19347 and RM19352 on Chr.6, with a physical distance of 106.3 kb. Sequencing of candidate genes revealed that an 83-bp fragment loss and a base substitution occurred in the LOC_Os06g04540 gene in the mutant, confirming preliminarily that the LOC_Os06g04540 gene was the MFS3 candidate gene. Subsequent qPCR analysis showed that the mutation caused the down-regulation of OsMADS1 and FON1 genes, and the up-regulation of OsIDS1 and SNB genes, which are all involved in the regulation of spikelet development. The MFS3 mutation also significantly reduced the transcription of the REP gene, which is involved in palea development. These results indicated that the MFS3 gene might be involved in the spikelet meristem determinacy and palea identity by regulating the expression of these related genes.